Propagación vegetativa del plátano maqueño (musa paradisiaca l.) Aplicando bencil amino purina (BAP) y ácido indolacético (AIA) - Zambrano Uriña, Nancy Yaritza (2022)
The absence of propagation materials under optimal conditions considerably limits the development of plantain plantations of varieties such as maqueño. From there, the development of the present work arose, which sought to determine the vegetative propagation of maqueño plantain by applying Benzyl Amino Purine (BAP) and Indoleacetic Acid (AIA) through the establishment of an experimental plot located in the Velasco Ibarra canton in the province of Guayas. For this purpose, a Completely Randomized Design (CRD) was applied, with four treatments and an equal number of replications, with six experimental units (corms) each. The Tukey test (p≤ 0.05) was used to compare means between treatments, while the variables studied were: number of shoots, shoot diameters, shoot length, shoot vigor, shoot survival and economic analysis. Regarding the results achieved, statistical equality was observed in each of the variables studied (p->0.05); however, in variables such as shoot length and diameter, a slight numerical superiority of the hormonal treatments (T2, T3 and T4) in relation to the control was observed. Finally, although the treatment that reached a higher income was T3 with $68.00, the control (T1) reached a higher profitability (1228,00%), due to a higher number of shoots produced and a lower total cost.